Transportable and Ultra-Stable Laser System for 133Cs Rydberg Excitation - Zhongxiao Xu; Changtao Zhao; Donghao Li (Photonics)
Recent progress in Rydberg atoms has enabled a wide range of applications in quantum sensing and quantum computation. In these applications, ultra-stable optical reference systems are essential to meet the requirements of a narrow linewidth and low technical noise. However, most existing systems are confined to laboratory settings and are not suitable for measurement-site-independent applications, such as external electric field sensors. This paper presents a transportable ultra-stable optical reference system for Rydberg excitation. The system is based on a 10 cm long ultra-low-expansion glass optical cavity, and it achieves finesse values of 410 k (at 1018 nm) and 200 k (at 852 nm). After being assembled in the experimental environment, it can still operate with only minor adjustments even after being transported over 400 km. Thanks to its vibration-insensitive design, two-stage temperature control, and hybrid locking unit, the system can maintain its locking status for up to 2 h.